2018
DOI: 10.1111/den.13010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between endoscopic and laparoscopic removal of gastric submucosal tumor

Abstract: Results: The ER group had a significantly higher percentage of intraluminal growing type of tumor (100% vs 41%) and smaller tumor size (23 vs 33 mm) than the LR group. The ER group had a significantly shorter operative time (93 vs 145 min) and less blood loss (13 vs 30 mL) than the LR group. In the ER group, three patients who had tumors located on the anterior wall of the stomach required laparoscopic closure after EFTR because of difficulty in endoscopic closure of the gastric-wall defect. Postoperative comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 30 publications
5
55
1
Order By: Relevance
“…Of these potential papers, 35 were excluded (▶ Table 1). Finally, 15 original articles were included in final analysis [10][11][12][22][23][24][25][26][27][28][29][30][31][32][33]. A flow diagram summarizing the procedure of study selection is presented in ▶ Fig.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these potential papers, 35 were excluded (▶ Table 1). Finally, 15 original articles were included in final analysis [10][11][12][22][23][24][25][26][27][28][29][30][31][32][33]. A flow diagram summarizing the procedure of study selection is presented in ▶ Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…The per-lesion rate of surgical conversion was 0.8 %. Conversion to surgery was reported in three studies [12,30,32], who described one, three, and two cases of surgical conversions, respectively. Among the six cases of surgical conversion reported across the included studies, laparoscopic surgery was performed in all cases.…”
Section: Primary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastric submucosal tumors (G‐SMT), such as gastrointestinal stromal tumors (GIST), often arise from the muscularis propria, which consists of at least two layers (inner circle and outer longitudinal muscle). Laparoscopic and endoscopic cooperative surgery or endoscopic resection has been carried out for G‐SMT . However, these procedures require closure of the gastric wall.…”
Section: Brief Explanationmentioning
confidence: 99%
“…A retrospective study comparing endoscopic and laparoscopic resection of gastric submucosal tumors found endoscopic resection to require shorter operative times, less blood loss, and no difference in postoperative complications. 22 While these procedures are currently less invasive, safe, and feasible, a lag in incorporation into national guidelines will likely exist until long-term data are available and results are replicable outside of centers of excellence.…”
Section: Procedures For Resection Of Submucosal Tumorsmentioning
confidence: 99%